ANALISIS KINERJA BANK SYARIAH DENGAN METODE MAQASID INDEX SYARIAH DI PT BANK SYARIAH MANDIRI TAHUN 2013-2018 - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
Measurement of Islamic banking performance which focuses on achieving maqashid syari'ah was developed by Mustafa Omar Mohammed, Dzuljastri Abdul Razak and Fauziah MD Taib. They have developed a performance measurement for Islamic banking in the form of the sharia maqasid index (SMI). This study analyzes the performance of independent Islamic banks in terms of maqashid sharia 2013-2018. The object examined in this study is Bank Mandiri Syariah in Indonesia. The data used are annual financial reports for the period 2013-2018. The quantitative method used in this study uses the index number method. The index number method is useful if we want to know the development of a state in a macro, or the whole of the variables or events we observe.